MODELIZATION OF AMYLOID FIBRIL SELF-ASSEMBLY - V. Trusova; G. Gorbenko (East European Journal of Physics, 2018)
Intermolecular noncovalent interactions between protein molecules result in the formation of a wide spectrum of supramolecular assemblies the structure of which varies from disordered amorphous aggregates to the crystals with strictly defined translational symmetry in three directions. One-dimensional protein aggregates (amyloid fibrils) represent highly ordered semiflexible polymers with unique mesoscopic properties which can be tuned by both intrinsic physicochemical characteristics of polypeptide chain and milieu conditions. In the present work the molecular mechanisms of amyloid formation are discussed and mathematical description of the existing models of protein fibrillization are given. For disease-related amyloids, deeper understanding of fibril growth process may shed light on the pathogenesis and molecular mechanisms of the disorders, as well as on the strategies of amyloidosis prevention at atomistic level. In the context of nanotechnology and functional material science, knowing the details of amyloid formation is crucially required for the design of novel nanomaterials with unprecedented qualities.